Study on Factors Affecting Employee Turnover in Banking and Automotive Sector of Pakistan - Madiha Tanveer; Abdur Rehman; Muhammad Haris (International Journal of Experiential Learning & Case Studies, 2023)
This research is based on a study to investigate the impact of various factors affecting employee turnover in Pakistan's banking and automotive sector. A comprehensive literature review has been performed based on various hypotheses developed. Further, a survey strategy has been adopted to collect quantitative data. To test the hypothesis number of statistical methods have been implemented using SmartPLS. Both measurement and structural models have been developed for detailed analysis of variables affecting employee turnover. Results obtained from various analyses have also been discussed. Hence, this study examines the effect of employee engagement, job satisfaction, job insecurity, and work overload mediated through job stress and performance management on the intentions of an employee switching their job role. This study will not only assist in improving the effectiveness of retention strategies but also give updates about future retention strategies by analyzing the data collected and its results. The discovery of this study would encourage the uplifting of retention practices in other sectors as well.